The Correlation between Ways of Learning toward English Achievement at the First Year Students of SMPN 1 Banyakan - Yanti Ramiasih, M.Pd (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2021)
The aim of this research is to know whether there is any significant correlation between ways of learning toward English achievement at the first-year students of SMPN 1 BANYAKAN. The design used was a descriptive quantitative correlation research design. It was conducted in SMPN 1 BANYAKAN with the population was 252 of the first-year students of SMPN 1 BANYAKAN. While the sample of this research was 155 students. The instruments used in this research were questionnaire, test, and documentation. The data gotten was analyzed by SPSS version 20. to find descriptive and product moment. The results of the research were: the students’ ways of learning belong to “good” while the percentage is 45,3% and English achievement belongs to the “very low” category while the percentage is 32,4%. From the interpretation, data is “very low correlation” and negative with the score is -0.067 and not significant. Keywords: Correlation, Ways of learning, and English achievement